35.1k views
4 votes
ANSWER CORRECTLY OR DONT ANSWER AT ALL

ANSWER CORRECTLY OR DONT ANSWER AT ALL-example-1
ANSWER CORRECTLY OR DONT ANSWER AT ALL-example-1
ANSWER CORRECTLY OR DONT ANSWER AT ALL-example-2
ANSWER CORRECTLY OR DONT ANSWER AT ALL-example-3
ANSWER CORRECTLY OR DONT ANSWER AT ALL-example-4
ANSWER CORRECTLY OR DONT ANSWER AT ALL-example-5

1 Answer

0 votes

Answer:

5) A

6) C

7) B

8) D

9) D

10) A

11) C

12) C

Explanation:

5) The graph of an exponential decay function approaches zero, as the values of x grows bigger and bigger.

From the graph, it is only the first graph the has the end behavior of an exponential decay function.

The correct answer is A) I only

6) The given function is
y=2(3^x).

From x=1 to x=3, the grows by a factor of
3^(3-1)=3^2=9

From x=5 to x=7, the exponential function grows by a factor of
3^(7-5)=3^(2)=9

The correct answer is C.

7) The initial value of the car is $20,000.

Since the car loses 20% of its value every year, it has a multiplicative rate of change of
r=(4)/(5)

Hence the value will decay exponentially.

The correct answer is B.

8) Let the initial population be
P_0, then after 210 minutes,
P=2P_0

This implies that:
2P_0=P_0e^(210k)


\implies k=(\ln(2))/(210)

With initial population is
P_0=8000, we want to find the population after 630 minutes.


P=8000e^{(\ln(2))/(210)*630}=64000

The correct answer is D

9)

Let the initial population be
P_0, then after 60 minutes,
P=3P_0

This implies that:
3P_0=P_0e^(60k)


\implies k=(\ln(3))/(60)

With initial population is
P_0=2000, we want to find the population after 240 minutes.


P=2000e^{(\ln(3))/(60)*240}=162000

The correct answer is D

10) The initial cost is $40 the unit rate per visit to the Gym is

$2

The total cost y, is given by:
y=2x+40, where x is the number of visit.

With $90, you substitute y=90 and solve for x.


2x+40=90


2x=50\\x=25

The correct answer is A

11) Let
f(x)=3x+2, then
f(x+2)=3(x+2)+2=3x+6+2=3x+8


f(a+2)-f(a)=3a+8-(3a+2)=3a+8-3a-2=6

Therefore the correct answer is C.
y=3x+2

12) Let
f(x)=7(0.5)^x, then
f(x+2)=7(0.5)^(x+2)

This implies that:


(f(a+2))/(f(a))=(7(0.5)^(x+2))/(f(7(0.5)^(x))= (7(0.5)^(x)*0.5^2)/(f(7(0.5)^(x))=(0.5^2)/(1)=(1)/(4)

The correct answer is C

User Paulo Belo
by
4.0k points